Shunt Capacitors Placement in Kurdistan Region Power System Using Power Losses Index - Mohammed, Dara H. Amin; Husain, Mohammed A.; Abbas, Najimaldin M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
Capacitors in power systems are generally used to supply reactive power for the purpose of loss minimization and voltage profile improvement. The shunt capacitor allocation problem is the determination of the location of the capacitor to be placed in power system in a manner to reduce the total power losses of the networks. In this paper loss determination and capacitor placement is studied to reduce power loss in KRPS (Kurdistan Region Power System) using PSAT program under MATLAB Software. The capacitor placement problem aims to determine the locations of capacitors to be installed in a KRPS based on an index called power losses index (PLI) which it indicates the most effective candidate buses that the capacitor banks to be installed. The objective of the paper is aimed to reduce the power losses in the system and retain the voltage magnitudes of the system within prescribed maximum and minimum allowable values.
Keywords: Capacitor Location; Power Loss Reduction; Voltage Profile; KRPS; Power Losses